2002
DOI: 10.1108/09544780210425892
|View full text |Cite
|
Sign up to set email alerts
|

Leadership ethical dimension: a requirement in TQM implementation

Abstract: Deals with theoretical arguments that justify why the leadership of managers and its ethical dimension is a powerful enabler for TQM efforts to sustain, together with a systematic management. Starts by setting out a multidimensional conception of leadership in which the ethical sphere is explicitly considered. The principles articulating TQM are then analysed, studying the role of leadership and its ethical dimension, in their implementation. Concludes with five propositions, stating that the explicit consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
5

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 28 publications
3
30
0
5
Order By: Relevance
“…He points out how total quality management requires leadership which will have an impact on behaviour modification and changing people's attitudes. Other writers also emphasise the importance of leadership (Hansson, 2001;Kanji and Moura E Sa  , 2001;Rao Tummala and Tang, 1996) and the requirement of a leader who can develop trust based on past behaviour (Carroll, 2000;Godfrey et al, 1997;Harris and Hartman, 1992) and ethical leadership (Gonza  lez and Guille Ân, 2002). A study of UK hotel chains has suggested that effective communication is a primary requirement of effective strategy implementation, although it does not guarantee the effectiveness of the implementation (Peng and Littlejohn, 2002).…”
Section: Models Excellence and Implementation Issuesmentioning
confidence: 97%
“…He points out how total quality management requires leadership which will have an impact on behaviour modification and changing people's attitudes. Other writers also emphasise the importance of leadership (Hansson, 2001;Kanji and Moura E Sa  , 2001;Rao Tummala and Tang, 1996) and the requirement of a leader who can develop trust based on past behaviour (Carroll, 2000;Godfrey et al, 1997;Harris and Hartman, 1992) and ethical leadership (Gonza  lez and Guille Ân, 2002). A study of UK hotel chains has suggested that effective communication is a primary requirement of effective strategy implementation, although it does not guarantee the effectiveness of the implementation (Peng and Littlejohn, 2002).…”
Section: Models Excellence and Implementation Issuesmentioning
confidence: 97%
“…Gonzalez and Guillen (2002) carried on the discussion of the administrator's leadership style and ethical belief influence on TQM implementation, and the results of the study showed that leadership really has suitable influence on TQM. This meant that the relationship between leader and followers was setting up in the followers' trust, which appealed to the leader.…”
Section: Continuous Improvementmentioning
confidence: 98%
“…The discussion is based on empirical data obtained from the questionnaires and is supplemented by information obtained during the face-to-face interviews with informants from all the four local authorities. Seven variables which researchers such as Ahmad Sarji (1996a), Saffiee (2000), Gonzalez and Guillen (2002) and Kafayah Amar and Zuraidah Mohd Zain (2002) have argued are essential elements in the implementation of quality management are included in the discussion. Exploratory factor analysis (EFA) was used to identify the perceived factors which determine the successful implementation of quality management.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Teamwork is also an important factor that contribute to the successful implementation of quality management in an organisation (Ahmad Sarji, 1966a;Saffiee, 2000;Gonzalez & Guillen, 2002). Teamwork needs to be practised in a number of forms.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation